2010
DOI: 10.1016/j.neuroimage.2009.10.067
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructure underlying default mode network connectivity in the human brain

Abstract: White matter microstructure underlying default mode network connectivity in the human brain, NeuroImage (2009), doi:10.1016/j.neuroimage.2009.10.067 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(132 citation statements)
references
References 54 publications
7
119
0
4
Order By: Relevance
“…B Simplified illustration of the principal regions for the two anticorrelated networks, the DMN (red) and TPN (blue volunteers, and found some regions that have corresponding structural fiber pathways, such as the pCC/ PCUN projection to mPFC and bilateral mTLs that has significant functional connectivity, while some significant functional connections, such as that between mPFC and mTLs, exist without known underlying direct fiber tracts [8]. Of note, fiber tracts in the DMN, such as those connecting pCC to bilateral mTLs [20], and pCC to mPFC [21,22], are also detectable between homologous regions in nonhuman primates using effective tracers, suggesting the effectiveness of in vivo DTI tractography in tracing tracts. Subsequent neuroimaging studies [19] combining DTI tractography and fc-fMRI have confirmed a relationship between functional and anatomical connections within the DMN in agreement with Greicius et al [8], further implying that regions that are connected directly by fiber tracts also have significant functional connections, but the inverse condition need not be true because functional connections might be linked indirectly via multisynaptic connections or more distant cortical regions.…”
Section: Connectivity Within the Default Mode Networkmentioning
confidence: 99%
“…B Simplified illustration of the principal regions for the two anticorrelated networks, the DMN (red) and TPN (blue volunteers, and found some regions that have corresponding structural fiber pathways, such as the pCC/ PCUN projection to mPFC and bilateral mTLs that has significant functional connectivity, while some significant functional connections, such as that between mPFC and mTLs, exist without known underlying direct fiber tracts [8]. Of note, fiber tracts in the DMN, such as those connecting pCC to bilateral mTLs [20], and pCC to mPFC [21,22], are also detectable between homologous regions in nonhuman primates using effective tracers, suggesting the effectiveness of in vivo DTI tractography in tracing tracts. Subsequent neuroimaging studies [19] combining DTI tractography and fc-fMRI have confirmed a relationship between functional and anatomical connections within the DMN in agreement with Greicius et al [8], further implying that regions that are connected directly by fiber tracts also have significant functional connections, but the inverse condition need not be true because functional connections might be linked indirectly via multisynaptic connections or more distant cortical regions.…”
Section: Connectivity Within the Default Mode Networkmentioning
confidence: 99%
“…One possible reason for altered large-scale network activation with increasing age is that ageing leads to widespread neurobiological changes, which impact the structural organization and integrity on which large-scale networks critically depend (Greicius et al, 2009;Horn et al, 2013;Van den Heuvel et al, 2008;Teipel et al, 2010). Thus, structural changes related to ageing would, in part, account for the functional changes associated with cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Early research on this topic focused on relating FC to AC within few regions in the brain (Koch et al 2002;Guye et al 2003;Boorman et al 2007;Cohen et al 2008;Zhou et al 2008;Takahashi et al 2008). There is also strong evidence that anatomical networks support the formation of functional patterns of resting state connectivity (van den Heuvel et al 2008;Skudlarski et al 2008;Greicius et al 2009;van den Heuvel et al 2009;Teipel et al 2010). Disruption of this FC-AC dependence has been thought to result in significant behavioural deficits related to disconnection syndromes such as schizophrenia (Skudlarski et al 2010;Camchong et al 2011).…”
Section: Introductionmentioning
confidence: 99%